Engineering Organoid Vascularization - Grebenyuk, Sergei; Ranga, Adrian (Frontiers in Bioengineering and Biotechnology, 2019)
The development of increasingly biomimetic human tissue analogues has been a long-standing goal in two important biomedical applications: drug discovery and regenerative medicine. In seeking to understand the safety and effectiveness of newly developed pharmacological therapies and replacement tissues for severely injured non-regenerating tissues and organs, there remains a tremendous unmet need in generating tissues with both functional complexity and scale. Over the last decade, the advent of organoids has demonstrated that cells have the ability to reorganize into complex tissue-specific structures given minimal inductive factors. However a major limitation in achieving truly in-vivo-like functionality has been the lack of structured organization and reasonable tissue size. In-vivo, developing tissues are interpenetrated by and interact with a complex network of vasculature which allows not only oxygen, nutrient and waste exchange, but also allow for inductive biochemical exchange and a structural template for growth. Conversely, in-vitro, this aspect of organoid development has remained largely missing, suggesting that these may be the critical cues required for large-scale and more reproducible tissue organization. Here, we review recent technical progress in generating in-vitro vasculature, and seek to provide a framework for understanding how such technologies, together with theoretical and developmentally inspired insights, can be harnessed to enhance next generation organoid development.